Stakeholder Consultation: Regional Needs and Priorities for Climate Information Services - List, Geneva; Zebiak, Stephen E.; Rose, Alison (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
A stakeholder consultation was conducted to identify needs and priorities for climate information services (CIS) in target countries. As part of AICCRA, Accelerating Impacts of CGIAR Climate Research for Africa, the results will inform a CIS cost and benefit toolkit that will contribute to the tailoring and targeting of CIS packages for small-scale farmers and livestock keepers. Stakeholders were asked to identify CIS needs, priorities, decisions, barriers, and gender equity considerations as well as preferences for scaling. Data were also collected on the preferences of outcome variables to quantify in the cost and benefit toolkit. Findings from the consultation highlight the need for multi-stakeholder collaboration and the importance of addressing communication barriers and CIS awareness-raising. Gender-responsive CIS require targeting and tailoring that consider women’s roles and ongoing inequities or constraints that can limit CIS deployment and impacts. Several respondents identified the importance of private sector engagement and public-private partnerships in particular to support CIS communication and delivery. There is an opportunity to introduce more comprehensive CIS that provide tailored recommendations across socio-economic groups leveraging climate products already offered in the target countries.